A Delphi Study to Identify Personal Finance Core Concepts and Competencies of First‐Generation College Students. (March 2015) - Kabaci, M. J.; Cude, Brenda J.
<x xml:space="preserve">Abstract</x> The purpose of this study was to gain consensus among researchers and college educators using the Delphi method about the personal finance knowledge, skills, and actions/behaviors that are important for all first‐generation college students. A group of five experts who had knowledge of college students' financial literacy needs participated as panelists. Three rounds of questionnaires elicited responses from the panelists to identify personal finance core concepts and competencies that are most crucial for first‐generation college students. All 14 personal finance concepts and 234 competencies gained consensus. The mean rankings by importance of each personal finance concept and competency were identified.